2019
DOI: 10.1186/s40478-019-0873-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of somatic CNVs in brains of synucleinopathy cases using targeted SNCA analysis and single cell sequencing

Abstract: Synucleinopathies are mostly sporadic neurodegenerative disorders of partly unexplained aetiology, and include Parkinson’s disease (PD) and multiple system atrophy (MSA). We have further investigated our recent finding of somatic SNCA (α-synuclein) copy number variants (CNVs, specifically gains) in synucleinopathies, using Fluorescent in-situ Hybridisation for SNCA, and single-cell whole genome sequencing for the first time in a synucleinopathy. In the cingulate cortex, mosaicism levels for SNCA gains were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 119 publications
4
42
0
Order By: Relevance
“…There is also evidence at the genetic level that the cingulate cortex is an important region in PD. Perez-Rodriguez et al [35] found somatic copy number variant gains (gene duplicates or triplicates) of SNCA, the gene encoding alpha-synuclein, in the cingulate cortex. These post-zygotic mutations were >2% higher in neurons in the cingulate cortex of patients diagnosed with alpha-synucleinopathies than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence at the genetic level that the cingulate cortex is an important region in PD. Perez-Rodriguez et al [35] found somatic copy number variant gains (gene duplicates or triplicates) of SNCA, the gene encoding alpha-synuclein, in the cingulate cortex. These post-zygotic mutations were >2% higher in neurons in the cingulate cortex of patients diagnosed with alpha-synucleinopathies than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent population studies have yielded PD heritability rates ranging between 0.22 and 0.27 ( 32 , 35 ), suggesting that a majority of cases may be due to the interaction of genetic and environmental factors [rural living and pesticide exposure are well-known risk factors, while tobacco, coffee, and moderate alcohol consumption may be protective, see review ( 36 )], and to stochastic processes. Mosaicism may for instance be a non-negligible contributor to the pathogenesis of sporadic PD ( 37 ), as changes in copy numbers of the SCNA gene have been observed in patient SN DA neurons ( 38 ). Nevertheless, only a minor fraction of the disease's heritability (16–36% depending on its prevalence) can be explained by the most recently identified risk loci ( 32 ), indicating that much of the “missing heritability” remains yet to be uncovered.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The role and contributions of SNCA in different neurodegenerative disorders remains partially understood. SNCA mutations are only identified in a minority of PD and other synucleinopathy patients (39), with most synucleinopathy cases occurring in the absence of defined mutations or in the context of interacting polygenetic, epigenetic, and environmental contributions to synucleinopathy risk (6,7). In this study, single-cell analysis reveals clear variations in SNCA expression by cell type in human ACC and MTG samples, with striking differences in SNCA expression by excitatory versus inhibitory neurons and other cell types.…”
Section: Discussionmentioning
confidence: 63%